El líder - Clifton, Jim; Harter, James K. (BookaVivo, 2022)
Who will manage the work teams in a context of profound changes? Gallup has found that the ability and excellence of managers and team leaders are the single most important factor in an organization's long-term success. This book shows leaders and managers how to adapt their organizations to constant changes, such as the demands of new workplaces, remote employee management, the development of artificial intelligence, project work. or the recruitment and retention of the best employees. Based on the largest global study on the future of work. It offers the resources to optimize the potential of the members of a team and drive the growth of an organization.